Cytotoxicity and Apoptotic Inducibility of Methanol Extracts of Bruguiera Gymnorrhiza and Aegialitis Rotundifolia Against HepG2 and MCF-7 Cell Lines - A.R.K REDDY; J. RATNA GRACE (International Journal of Pharma and Bio Sciences, 2018)
The purpose of the present study was to investigate the methanolic extract of Bruguiera gymnorrhiza and Aegialitis rotundifolia for their cytotoxic and apoptotic induction activities. The cytotoxic activity was evaluated by MTT assay against hepG2 and MCF7 Cell lines. Induction of Apoptosis was carried hepG2 cell line. Morphological changes and DNA fragmentation were found up on incubation with extract. Both the plant extracts showed significant cytotoxic activity against hepG2 and MCF7 cell lines and the concentration required for 50% cell death was 77.29 µg/ml, and 99 µg/ml for Bruguiera gymnorrhiza; 97.77 µg/ml and 165.34 µg/ml for Aegialitis rotundifolia against hepG2 and MCF7 cell lines respectively. Thus from the present investigation it can be concluded that the methanolic extract of Bruguiera gymnorrhiza and Aegialitis rotundifolia exhibit both Apoptosis induction and Cytotoxic activities.